2020
DOI: 10.1136/bmjsem-2019-000729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knee arthroplasty on sports participation and activity levels: a systematic review and meta-analysis

Abstract: ObjectiveDesires and expectations of patients in regard to resume participation in sport activities after knee arthroplasty strongly increased in recent years. Therefore, this review systematically reviewed the available scientific literature on the effect of knee arthroplasty on sports participation and activity levels.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase, SPORTDiscus and reference lists were searched in February 2019.Studies eligibility criteriaInclusion of knee osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
(48 reference statements)
2
12
0
2
Order By: Relevance
“…An mounting amount of evidence, including the review by Konings and colleagues, 5 suggests that knee arthroplasty provides a window of opportunity to improve physical activity. As the number of 'younger' knee arthroplasty patients will likely rise in coming years, this opportunity should be taken to provide better participation-based care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An mounting amount of evidence, including the review by Konings and colleagues, 5 suggests that knee arthroplasty provides a window of opportunity to improve physical activity. As the number of 'younger' knee arthroplasty patients will likely rise in coming years, this opportunity should be taken to provide better participation-based care.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines can, among others, be based on evidence provided by Konings and colleagues. 5 Unfortunately, evidence in this review was based on self-reports of physical activity and sports, while more information from device-based measurements of those activities is needed.…”
Section: The Importance Of Physical Activity and Other Forms Of Societal Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with higher quality evidence have focused on patient-reported outcome measures (PROMs) and other outcomes. In their 2020 meta-analysis of RTS after knee arthroplasty, Konings et al 31 reported the level of participation with several postoperative sporting activities and a greater focus on TKA than UKA. 31 Belsey et al 4 compared RTS after UKA and high-tibial osteotomy (HTO) in their meta-analysis, with a singular focus on PROMs and the ability to return to physical activity between these 2 groups.…”
mentioning
confidence: 99%
“…In their 2020 meta-analysis of RTS after knee arthroplasty, Konings et al 31 reported the level of participation with several postoperative sporting activities and a greater focus on TKA than UKA. 31 Belsey et al 4 compared RTS after UKA and high-tibial osteotomy (HTO) in their meta-analysis, with a singular focus on PROMs and the ability to return to physical activity between these 2 groups. The only similar high-quality study to date is by Witjes et al, 52 who performed a meta-analysis in 2016 comparing RTS in both TKA and UKA but with a greater focus on PROMs.…”
mentioning
confidence: 99%